Content Analysis of Linguistic Characteristics of Foreign Language Use in Korean Magazine Advertising - Yang, Wonmo; Han, Sangpil (International Journal of Advanced Science and Technology, 2019)
Background/Objectives: The purpose of this study is to examine the linguistic and expressive characteristics used in Korean magazine advertisements. Methods/Statistical analysis: Use of foreign language is an important trend in advertising content.  Relatively few studies have analyzed foreign language in advertising content. This study reviewed the content of Korean magazine advertising from 1995 to 2015 using the content analysis method. Findings: The present article found that the number of Korean magazine advertisements with a foreign language was not significantly different longitudinally from the 1990s to the 2010s.   The results of the three research questions showed that there was not a significant change in the usage of foreign languages in the studied years. However, the results of this study showed that there was a significant difference in the advertising appeal of using foreign languages in general women’s magazines.  The results also showed that Korean magazine advertising used foreign language in anappropriate way, which implies that using foreign language is more effective than using domestic language for informing and persuading consumers in a market. Improvements/Applications: The findings of the study provide a unique view of the field to researchers and advertisers, including directions for future research and practical implications for advertising creative research.Keywords: Content analysis, Foreign language in advertising, Advertising content, Advertising appeal, Advertising copy